Exploring the Legal and Policy Implications of Non-Fungible Tokens - Mochammad Tanzil Multazam (Universitas Muara Bungo, 2022)
Legal and policy issues surround NFTs. This study examines NFT legal and policy issues and their effects on the digital economy. This study showed that NFTs could revolutionize digital asset ownership, but they also raise questions about intellectual property, privacy, and taxes. As NFT ownership evolves, buyers and sellers must understand their legal rights and obligations and avoid infringing on others' intellectual property rights. NFTs with photos or other personal data raise privacy concerns. To avoid privacy violations, buyers and sellers should consider NFT privacy implications. NFTs may be used for money laundering or terrorism. Regulators and law enforcement closely monitor NFT transactions to prevent misuse. Policymakers, regulators, and industry participants trying to establish a clear and effective legal framework that protects all parties should consider this study. These legal and policy issues must be addressed as NFTs gain popularity to maximize their potential. NFTs are legally and politically complex. This study emphasizes the need for ongoing research and stakeholder collaboration to responsibly and legally use NFTs and realize the digital economy's transformative potential.